SMOKING BEHAVIOR, SOCIAL SUPPORT, AND CESSATION MOTIVATION IN SMOKING AMONG HEALTH SCIENCES’ STUDENTS - Melizza, Nur; Kurnia, Anggraini Dwi; Masruroh, Nur Lailatul; Yulianti, Indrasari Dwi (Jurnal Keperawatan, 2020)
ABSTRACT Introduction: Many students have been accustomed to smoking, including those majoring at health sciences. Theoretically, they are supposed to be the ones who are actively aware of some possible health damages caused by smoking habit. Thus, people around them play an essential role in taking control of someone?s pattern through social support, especially over those who are highly motivated to quit smoking. Objective: This study aimed to identify smoking behavior, social support, and cessation motivation in smoking among health sciences? students. Methods: This research was categorized as observational-descriptive one, with the use of accidental sampling technique to recruit as many as 63 students of faculty of health sciences who were defined as active smokers. The data, furthermore, were collected by means of a questionnaire. At last, a statistical-descriptive analysis was used to evaluate the data. Result: The result was most of the involved respondents were shown to have a moderate trend of smoking (65%). On the other hand, the majority of the respondents had been supported through some types of social support with relatively high percentage, to name appraisal support (indicating 71%), tangible support (indicating 87%), self-esteem support (indicating 97%), and belonging support (indicating 92%). Moreover, most of the respondents were equipped by the high level of quittance motivation from smoking, signifying 71%.  Discussion: This research had indicated that the level of smoking habit perceived by the respondents was moderate. In short, appraisal support was defined as high, tangible support low, self-esteem support high, and belonging support high. In addition, some of the respondents had demonstrated a high level of quittance motivation from smoking